Strategy of delayed intervention without stent implantation in myocardial infarction with ST segment elevation caused by massive thrombosis of the infarct-related artery - A. V. Azarov; M. G. Glezer; A. S. Zhuravlev; I. R. Rafaeli; S. P. Semitko; K. V. Gyul’misaruyan; S. A. Kurnosov (Евразийский Кардиологический Журнал, 2023)
Aim. TIntroduction. To evaluate in-hospital angiographic  and five-year posthospital clinical outcomes  of percutaneous  intervention strategy without stent implantation with immediate coronary  artery stenting technique in STEMI patients  with massive coronary thrombosis.Material and methods. The  study  enrolled  116  patients  with primary STEMI myocardial  infarction with the signs  of massive  thrombosis  in the lumen of the main  epicardial  coronary   artery with TIMI thrombus  grade  greater  than 3 after antegrade blood  flow restoration. In the 1st group of delayed intervention at the primary stage the blood  flow was restored by small diameter balloon  inflation and/ or manual vacuum thrombus  aspiration until stable TIMI grade  3 blood   flow  was achieved,  at control  CAG on day 5-6  in 36 people  the stent was not implanted due to insignificance of infarct-related coronary  artery stenosis (stenosis less than 50% according  to QCA). Immediate stent implantation was performed  in 78 patients (group 2). The primary endpoint  was  the incidence  of adverse cardiovascular events, including total mortality, recurrent myocardial infarction, repeated revascularization of the infarct-responsive  artery. Secondary  endpoint: frequency of achieving optimal myocardial perfusion as  measured by  angiography – TIMI blood flow and Myocardial Blush Grade.Results. The median follow-up  period  was  47  months.  The incidence  of the primary end point (MACE) was 15,8%  in group 1 and 23,1%  in group 2, with no  statistically significant difference  (p=0,408).   Overall mortality (10,5% and 11,7%),  the rate of repeat myocardial infarction (2,6%  and 5,1%),  and the rate of repeat target vessel revascularization (2,6%  and 6,4%)  were without significant advantage between subgroups.  Optimal reperfusion (TIMI-3 and Myocardial Blush Grade 2-3  after primary procedure  was achieved  in significantly (p=0,02)  more patients in group 1 (89%)  than in group 2 (69,2%)  ST segment resolution ≥70% after intervention was achieved in 87%  of cases  in group 1 and in 64,1%  of cases in group 2 (p=0,011).Conclusion. In STEMI patients  with massive coronary thrombosis, the method of delayed percutaneous  intervention increases  the rate of achieving optimal blood flow  and allows  avoiding  stent implantation in the infarct-related artery in 50% of cases as compared to the method of immediate stenting. Both methods have comparable hospital and five-year clinical risks.